Women, vulnerability and HIV/AIDS : a rights perspective - Gomez, Adriana ed. (Latin American and Caribbean Women's Health Network SantiagoCL, 1998)
Looks at women and HIV/AIDS from the national perspectives. Focuses on aspects such as HIV/AIDS and reproductive health, HIV/AIDS; sexuality and gender; positive women; prevention strategies; and, the sex trade. Highlights the on-line debate.